2012
DOI: 10.1111/j.1532-5415.2011.03882.x
|View full text |Cite
|
Sign up to set email alerts
|

Frailty Transitions in the San Antonio Longitudinal Study of Aging

Abstract: OBJECTIVES To examine frailty transitions in Mexican American (MA) and European American (EA) older adults. DESIGN Longitudinal, observational cohort study. SETTING Socioeconomically diverse neighborhoods in San Antonio, Texas. PARTICIPANTS 312 MA and 285 EA community-dwelling older adults (65+) with frailty information at baseline (1992–96) and transition information at follow-up (2000–01) in the San Antonio Longitudinal Study of Aging (SALSA). MEASUREMENTS Five frailty characteristics (weight loss, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
156
6
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 172 publications
(179 citation statements)
references
References 28 publications
12
156
6
5
Order By: Relevance
“…18 Thus, it is believed that muscular strength and gait speed are of the utmost importance for elderly people, since it has been observed that loss of muscle mass 19 and low gait speed 20 are associated with negative outcomes in elderly persons, 20 among which are the establishment of frailty syndrome 19,20 and death. 5 Literature reports that this occurs due to the aging process tending to reduce muscle mass. 21 In this context, one can hypothesize that possible interventions and changes, even if subtle, such as for example, an increase in overall muscle strength and mobility of elderly individuals, could further enhance the transition towards improving their condition.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…18 Thus, it is believed that muscular strength and gait speed are of the utmost importance for elderly people, since it has been observed that loss of muscle mass 19 and low gait speed 20 are associated with negative outcomes in elderly persons, 20 among which are the establishment of frailty syndrome 19,20 and death. 5 Literature reports that this occurs due to the aging process tending to reduce muscle mass. 21 In this context, one can hypothesize that possible interventions and changes, even if subtle, such as for example, an increase in overall muscle strength and mobility of elderly individuals, could further enhance the transition towards improving their condition.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, muscle strength and gait speed remained relatively stable over time, and were the items that were most often positive for the phenotype in both evaluations, agreeing with the findings of previous studies. 5,8,18 A study carried out in 2012 by Espinoza et al 5 observed that muscle strength and gait speed are the most prevalent variables in frail elderly persons. Associated with this, previous studies concluded that the reduction of muscle strength is not only the main variable that contributes to the establishment of the frailty syndrome, 19 but also that lower muscle strength identified in the baseline assessment is associated with a negative evolution of the phenotype.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[3][4][5] The incidence and prevalence of frailty syndrome vary and are influenced by the geographic location studied, by socioeconomic factors such as education, and by age, such that its incidence and prevalence are higher among individuals aged 80 years or over. 2,3,[6][7][8][9][10] Studies conducted both in Brazil and in other countries have reported different prevalence rates, ranging from 6.9% to 40.6% among frail elderly individuals and 46.3% to 60.1% among prefrail individuals. 2,4,[11][12][13][14] In this regard, frailty syndrome should be targeted by earlier investigations and interventions, given its impact on elderly individuals, their families and society as a whole.…”
Section: Introductionmentioning
confidence: 99%